A Dynamic Model of Human and Livestock Tuberculosis Spread and Control in Urumqi, Xinjiang, China. (25th July 2016) - Liu, Shan; Li, Aiqiao; Feng, Xiaomei; Zhang, Xueliang; Wang, Kai
Abstract : We establish a dynamical model for tuberculosis of humans and cows. For the model, we firstly give the basic reproduction numberR 0 . Furthermore, we discuss the dynamical behaviors of the model. By epidemiological investigation of tuberculosis among humans and livestock from 2007 to 2014 in Urumqi, Xinjiang, China, we estimate the parameters of the model and study the transmission trend of the disease in Urumqi, Xinjiang, China. The reproduction number in Urumqi for the model is estimated to be 0.1811 (95% confidence interval: 0.123–0.281). Finally, we perform some sensitivity analysis of several model parameters and give some useful comments on controlling the transmission of tuberculosis.